The Impact of CPO Downstream Policy in Cooking Oil Industry on Indonesian Export Foreign Change - Asifa Asifa; Nia Kurniawati Hidayat; Novindra Novindra (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
Cooking oil is one of the derivatives of Crude Palm Oil (CPO) food products, which plays an important role in life and the economy. Government policies downstream, such as changes in export taxes and increasing the production capacity of the downstream cooking oil industry, are designed to encourage the development of cooking oil production. This study employs an econometric equation model with simultaneous equations to: (1) analyze the factors affecting CPO demand by the cooking oil industry; demand and supply, as well as palm cooking oil exports (2) analyze the impact of changes in export taxes; increasing CPO production capacity and the combination of these policies on foreign exchange earnings from cooking oil exports. The findings indicated that changes in Indonesia’s CPO export tax reduced the volume of CPO exports globally but increased domestic CPO supply. Consequently, CPO prices declined, leading to higher demand from the downstream industry. Increased demand for CPO and higher production capacity in the downstream industry were expected to boost cooking oil production further.